IMPLEMENTASI APLIKASI QUIZLET SEBAGAI MEDIA PEMBELAJARAN BAHASA INGGRIS: STUDI KASUS KUALITATIF TENTANG PENGALAMAN DAN PERSEPSI SISWA KELAS X DI MA YAA BUNAYYA - Kaipman, Paskalis; Tabuni, Demmy; Daullu, Melissa Aeudia; Trince, Merliana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to explore the implementation of the Quizlet application as an English learning medium at MA Yaa Bunayya, specifically in understanding the experiences and perceptions of 10th-grade students towards digital-based learning materials. The study used a qualitative approach with a case study design. Participants consisted of 13 10th-grade students and one English teacher as a key informant. Data were collected through in-depth interviews, learning observations, and documentation, then analyzed using thematic analysis. The results of the study revealed four main themes: the application of teacher pedagogy, a more visual and interactive student learning experience, positive perceptions of the benefits and convenience of Quizlet, and barriers such as network, devices, mobile phone interference, and the need for teacher assistance. These findings indicate that Quizlet can enrich vocabulary learning experiences, but its success depends on teacher direction, student readiness, and the classroom context. This study contributes to the study of technology-based English learning in madrasas.